Simplified Brain Organoids for Rapid and Robust Modeling of Brain Disease - Ha, Jeongmin; Kang, Ji Su; Lee, Minhyung; Baek, Areum; Kim, Seongjun; Chung, Sun-Ku; Lee, Mi-Ok; Kim, Janghwan (Frontiers in Cell and Developmental Biology, 2020)
Although brain organoids are an innovative technique for studying human brain development and disease by replicating the structural and functional properties of the developing human brain, some limitations such as heterogeneity and long-term differentiation (over 2 months) impede their application in disease modeling and drug discovery. In this study, we established simplified brain organoids (simBOs), composed of mature neurons and astroglial cells from expandable hPSC-derived primitive neural stem cells (pNSCs). simBOs can be rapidly generated in 2 weeks and have more homogeneous properties. Transcriptome analysis revealed that three-dimensional (3D) environment of simBOs facilitates the conversion of pNSCs to mature neuronal systems compared to a two-dimensional environment in the context of neurotransmitter release, synaptic vesicle formation, ion channels, calcium signaling, axonal guidance, extracellular matrix organization, and cell cycle. This result was correlated with the translocation of YAP1 into the cytoplasm by sensing matrix stiffness on the 3D models. Furthermore, we demonstrated that simBOs could easily be specified into midbrain-like simBOs by treatment with Shh and FGF8. Midbrain-like simBOs from a Parkinson’s disease patient (LRRK2G2019S)-derived pNSCs and gene-corrected (LRRK2WT) control pNSCs represented disease-associated phenotypes in terms of increased LRRK2 activity, decreased dopaminergic neurons, and increased autophagy. Treatment with the LRRK2 inhibitor, PFE-360, relieved the phenotype of Parkinson’s disease in midbrain-like simBOs. Taken together, these approaches could be applied to large-scale disease models and alternative drug-testing platforms.